The Influence of Good Corporate Governance Implementation and Company Size on Financial Performance: Evidence from Indonesian Banking - Muhammad Iqbal Juliansyah; Bulan Oktrima (Indonesian Financial Review, 2022)
This study aims to determine the effect of good corporate governance as proxied by an independent board of commissioners, board of directors, audit committee, institutional ownership and firm size on the financial performance of banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. The sampling method used is purposive sampling method, in order to obtain 17 sample banking for 3 years of observation which were downloaded from the Indonesia Stock Exchange website. The data analysis technique is panel data regression with the Eviews version 9.0 program. Partially, the Independent Board of Commissioners, Audit Commitees, Company Size variables have no significant effect on financial performance. However, the Board of Directors and Institutional Ownerships variables have significant effect on Financial Performance.